Iron metabolism in murine erythroleukaemic cells. - Peto, T; Rutherford, T; Thompson, J; Weatherall, D (1983)
In an attempt to develop a model system for analysing iron metabolism in a relatively homogeneous population of early red cell precursors, the intracellular distribution of 59Fe was examined in Friend murine erythroleukaemic cells after induction of haemoglobin synthesis with dimethylsulphoxide. After incubation of the cells with 59Fe-labelled transferrin, 59Fe was incorporated into haemoglobin, various ferritin fractions, and into the pellet obtained by centrifugation. No intracellular transferrin or low molecular weight compounds were found. In a series of 'chase' experiments 59Fe accumulated in haem, and some of this radioactivity appeared to be derived from the ferritin fraction. Extra iron could be mobilized from ferritin during chase experiments using iron deficient incubation medium. These studies indicated that, at least under these experimental conditions, ferritin iron in early red cell precursors can be utilized for haemoglobin synthesis.